Una magistratura castellana en Cataluña: Los alcaldes mayores del corregimiento de Manresa en el siglo XVIII - CERRO NARGÁNEZ, Rafael (Cuadernos de Historia Moderna, 2009)
In 1716 king Philip V established the Decree of Nueva Planta and articulated in Catalonia twelve castilian territorial districts (corregimientos). One of them was Manresa, integrated by the veguería of Manresa and subveguería of Berga (the latter was the subdelegation of the Intendencia). In this article, our objective was to study the sociological and professional profile of the alcaldes mayores. Their principal responsibilities were to give counsel in civil and criminal justice to the corregidores of this district, and presided the ayuntamiento during their absences. Definitely, our goal was to know better this royal officers, that played, in Catalonia, an important political and juridical role during 18th century.